Práticas sociais, memórias e vivências no combate à lepra: isolamento compulsório em asilos-colônia e preventórios brasileiros 1935 a 1986 - Silveira, Bruna Alves (2013)
This study represents a discussion about the social practices that are found on compulsory isolation, in asylums-cologne and preventions, of affected people through leprosy and healthy children. A practice that was considered the principal measure of fighting the disease, which was adopted by the Brazilian government from 1930 to 1986, period understood by the research. There was a public campaign that propagated the possibility of a unique quality of life, such as the objective of encouraging the hospitalization of the maximum of the \"sick\"as possible. As a matter of fact, the asylums-cologne were designed and constructed for that all of the necessities of the \"lepers\" were answered within the insulation. Those lepers stayed completely far away from the \"city\" and the \"healthy\" part of society. The provision of basic services such as housing and food, the performance of various social events, leisure activities and culture had been properly registered through different measures and was also confirmed by their own \"internal\" of the season. It was practically a life without burden for the residents of this area. Therefore, all of these qualities of life that are properly structured, was not sufficient to compensate for a life of confinement. Interviews, documentaries, photos and even poems written by \"ex-internal\" militate against authoritarian practices and hygienists, on behalf of which many subjects have lost their families, had homes torched, were caught by the police health as criminals, being thus robbed of their own lives and from the bosom of \"society\". Such social practices brought irreparable damage, on aspects of the social, psychological, financial and moral. Produced memories of horror, marked by fear, insecurity, frustration, pain and various traumas. Despite the isolation have become officially extinct in mid-1986, the terminology of the disease have been replaced officially by Hansen\'s disease by force of law, and the government has granted special pension indemnity of character to the subjects who were isolated on the basis of the disease, these memories that are still in dispute. It is in the development and redevelopment of experiences in isolation, in the fight for the right to this memory, which often manifests itself in patrimonial conservation of the old asylums or until the creation of museums within these spaces. Acknowledgement and for compensation for the children who have been deprived of the company of country, a fact that reverberated in the trajectory of their lives or in the search of new social practices, decoupling the idea of leprosy and approaching the current concepts about leprosy.